Utilização de fertilizantes a base de fosfito e micronutrientes na cultura do melão - Barreto, Norma Danielle Silva (Universidade Federal Rural do Semi-Árido, 2008)
Despite the high technology utilized in the melon crop at the Assú-Mossoró fruit producer area, state of Rio Grande do Norte, with respect to most of the nutrients, chiefly the micronutrients, the doses applied are the same as those utilized in regions of completely different edaphoclimatic characteristics, and most of the time defined by the supplier companies. Considering this fact, a study was aimed at to evaluate the response of the melon crop to foliar applied ferlizers containing fosfito and micronutrients. The experiment was carried out on a Red Latossolo Eutrophic soil, at Santa Júlia farm, municipality of Mossoró, utilizing a factorial scheme in randomized complete blocks design with four replications. The tratments were the combinations of fertilizers (Fosfitotal®, Fosfitototal Multielementos® and MicroUFERSA) and doses (0, 0.75, 1.5, 2.25 and 3.0 kg ha-1). The fertilizers were foliar applied prior to the beginning of flowering, through three sprayings at ten days interval. The traits evaluated were number, mean weight, and yield of marketable fruits (domestic and export markets), refuse and total, as well as pulp firmness and thickness, shape ratio, soluble solids content, titratable acidity, and laef nutrient content. Soluble solids content was higher in fruits of plants sprayed with Fosfitotal®, however the contents of P, Mg, Cu, Zn, and Fe decreased with increasing doses of the fertilizer. Plants that received the MicroUFERSA fertilizer had higher Mg, K, P,Cu, Mn, and Zn contents in leaves, which might have caused their higher yields. The highest net income was obtained with MicroUFERSA applied at the rate of 1.50 kg ha-1
Utilization of fertilizers containing phosphite and micronutrients in the melon crop
Keywords: Cucumis melo; Foliar applied fertilizers; Phosphite, micronutrients; Mineral nutrition; Cucumis melo; Fertilizantes foliares; Fosfito; Micronutrientes; Nutrição mineral; Pós-colheita; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA